Buenas prácticas de turismo sostenible para mejorar la gestión de los establecimientos de alojamiento turísticos de la ciudad de Riobamba - Chimborazo - Ponce Tualombo, Danilo Javier (2018)
The research project was carried out based on the theme of "Good Practices of sustainable tourism to improve the management of accommodation establishments of the city of Riobamba - Chimborazo ", taking into account the problematic of incorrect tourism management due to the non-use of good practices in tourism and the partial use of compliance with regulations and regulations, with a lack of knowledge of the current situation of the establishments of accommodation has an impact on the management of good practices with low levels of social responsibility, with parameters of good practices of sustainable tourism in the accommodation sector for its management, for these reasons many of the establishments of accommodation that do not interest and do not comply with the provisions established by the Good practices of sustainable tourism have sometimes led to a definitive closure of the establishment and in others to pecuniary sanctions by the regulatory bodies, the research has clearly defined objectives for the correct development of research, with a very broad state of the art which encompasses all the perceptions of national and international authors, a methodology with techniques and instruments that help the easy development of it, ending with the proposal description in which the results obtained within the work of research that will make a great contribution to housing establishments Tourism Management and Tourism Management which will have parameters for their evaluations.